Progress of High‑Performance Building Design with Cooling Load Variation from Solar Heat in HVAC Equipment Energy and Power and Operation - Zhou, Michael B. (New Energy Exploitation and Application, 2025)
Energy performance is one of the building performance related to the multiple disciplines. It is somewhat distinguishable to the LEED of Green Building Certificate Institute. The LEED uses the model design, e.g., adopting optimal pattern and parameter including the energy issue. The high‑performance design of building related to the energy applies the ASHRAE standard, code and guideline to calculate and predict their consumed and numerical quantity of the engineering power and energy need. The purpose of this paper is to study and apply the solar irradiation system and radiation, and to get the optimal energy kw‑hr (Btu) for the decarbonizations, reduction of GHG (Green House Gas) and decrease of the carbon footprint in construction with power KW (Btu/hr) capacity in the HVAC equipment and facilities of the building design. One strategy of seeking the goal is to look for the popular and practical design method for variable cooling load impacted by solar energy. After great efforts, the Radiant Time Series Method (RTS) based on the Excel codes has been found. The paper summarizes the logical procedure from the varied HVAC and building design codes and resources, creates the Excel computing codes, populates the case data, and assesses the computing outcome for the better building performance.